Measurements of the quality of working life in companies of the city of Córdoba 2021 - Castellano, Nélida del Carmen (2021)
Fil: Castellano, Nélida del Carmen. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Escuela de Graduados en Ciencias Económicas; Argentina.